2018
DOI: 10.1038/s41418-018-0103-x
|View full text |Cite|
|
Sign up to set email alerts
|

A p53/miR-30a/ZEB2 axis controls triple negative breast cancer aggressiveness

Abstract: Inactivation of p53 contributes significantly to the dismal prognosis of breast tumors, most notably triple-negative breast cancers (TNBCs). How the relief from p53 tumor suppressive functions results in tumor cell aggressive behavior is only partially elucidated. In an attempt to shed light on the implication of microRNAs in this context, we discovered a new signaling axis involving p53, miR-30a and ZEB2. By an in silico approach we identified miR-30a as a putative p53 target and observed that in breast tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 60 publications
(84 reference statements)
7
63
1
Order By: Relevance
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 .…”
Section: Discussionmentioning
confidence: 98%
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 .…”
Section: Discussionmentioning
confidence: 98%
“…Expression of miR-30a has been shown to be markedly reduced in patients suffering from triple-negative breast cancer with mutations in the TP53 gene, and this expression was negatively correlated with patient survival. Inactivation of p53 in these patients was associated with reduced miR-30a expression and an associated decrease in miR-30a-mediated suppression of ZEB2 expression, thereby leading to enhanced breast cancer cell plasticity, migration, and metastasis [6]. Other targets of miR-30a in breast cancer have also been identified as potential links between this miRNA and the regulation of metastatic progression, including vimentin, MTDH, and Eya2 [11,23,28].…”
Section: Biomed Research Internationalmentioning
confidence: 93%
“…Recently, accumulating evidence indicates that miRNAs may act as either tumor suppressors or oncogenes in the genesis of diverse cancer types [3,4]. The dysregulated expression of certain miRNAs, including miR-30 family members, has been closely linked to the onset and progression of breast cancer [5][6][7]. The miR-30 family includes 6 mature miRNAs (miR-30a, miR-30b, miR-30c-1, miR-30c-2, miR-30d, and miR-30e) that are separately encoded on chromosomes 1, 6, and 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we identified ZEB2 as a pivotal biomarker in glioma that promotes proliferation, migration, and invasion by inducing the epithelialmesenchymal transition (EMT) process and cell cycle progression (19). A recent study showed that ZEB2 was inhibited by several miRNAs, such as miR-153 (20), miR-155 (21), and miR-30a (22), and these interactions significantly suppressed the EMT process. On the other hand, ZEB2 was also found to regulate miRNA expression as a repressive transcription factor.…”
Section: Introductionmentioning
confidence: 99%